A VALIDATED REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR SIMULTANEOUS DETERMINATION OF FIVE ANTIEPILEPTIC DRUGS USED IN THE TREATMENT OF LENNOX–GASTAUT SYNDROME IN THEIR PHARMACEUTICAL DOSAGE FORMS - Hassib, Sonia T; M A Hashem, Hanaa; A Mahrouse, Marianne; A Mostafa, Eman (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Lennox–Gastaut syndrome (LGS) is mainly treated with antiepileptic drugs (AEDs) but using one AED is not sufficient to relieve all or even most patients. A combination of agents is usually preferred. In the current study, an isocratic, selective, sensitive, precise, and accurate reversed-phase high-performance liquid chromatography (RP-HPLC) method was developed for the simultaneous determination of rufinamide (RUF), lamotrigine (LAM), clonazepam (CLO), valproic acid (VAL), and diazepam (DIA) which are commonly used in the management of LGS in their dosage forms using lacosamide as internal standard. Methods: The method depends on using RESTEK C18 column (5 μm, 250 mm × 4.6 mm) and a mobile phase composed of acetonitrile:water (55: 45, v/v), pH = 3.3 adjusted with phosphoric acid. The method was conducted in an isocratic mode with a flow rate of 1ml/min and ultraviolet detection at 210 nm. Results: The linearity range was 2–40 μg/ml for RUF and DIA, 0.5–40 μg/ml for LAM and CLO, and 36–180 μg/ml for VAL. Conclusion: Statistical analysis revealed no significant difference between the results obtained and the official or reported ones for each cited drug. The method is simple to be easily implemented in quality control studies of the mentioned drugs in their pharmaceutical preparations.